Discovery of novel inhibitors targeting nematode chitinase CeCht1: Virtual screening, biological evaluation, and molecular dynamics simulation - Shen, Shengqiang; Ding, Baokang; Jiang, Xi; Yang, Meiling; Yang, Qing; Dong, Lili (Frontiers in Chemistry, 2022)
Plant-parasitic nematodes are a main limiting factor for worldwide agriculture. To reduce the global burden of nematode infections, chemical nematicides are still the most effective methods to manage nematodes. With the increasing resistance of nematodes, the development of new anti-nematicides drug is urgent. Nematode chitinases are found to play important roles in various physiological functions, such as larva moulting, hatching from eggshell, and host infection. Inhibition of nematode chitinase is considered a promising strategy for the development of eco-friendly nematicides. In this study, to develop novel nematode chitinase CeCht1 inhibitors, virtual screening of the ZINC database was performed using the pesticide-likeness rules, pharmacophore-based and docking-based approach in turn. Compounds HAU-4 and HAU-7 were identified as potent CeCht1 inhibitors with the IC50 values of 4.2 μM and 10.0 μM, respectively. Moreover, molecular dynamics simulations combined with binding free energy and free energy decomposition calculations were conducted to investigate the basis for the potency of the two inhibitors toward CeCht1. This work gives an insight into the future rational development of novel and potent nematode chitinase inhibitors.